Riobamba como Ciudad de las Primicias y su incidencia en el imaginario colectivo de los ciudadanos de 18 a 25 años del sector urbano, en el período enero-agosto 2015”. - Haro Guevara, Liset Narcisa (2017)
This research titled ¨Riobamba as a Novelty City and its incidence on the citizens’ collective imagination from 18 to 25 years of the urban sector, in the period January-August 2015. It is structured as follows: Introduction, Problem Statement and Justification, General and Specific objectives, State of the Art, Methodology, Results and Discussion, Conclusions and Recommendations. In the state of art from the historic section, different versions of authors are evidenced like Tomás Oleas, Helmer Carvajal, and others. On theoretical approximations of communication is quoted Neneka Pelayo and Adriana Cabrera, in addition to Dionne Santos, Juan Miguel Aguado, etc. Respect to imaginary authors such as Armando Silva, Néstor García Canclini, Manuela Cordero, among others. This research focused on approaches such as the Palo Alto School, which understands communication as a process of creating feelings from interaction and in the final analysis, the situations time-space, which will influence the behaviors. As methodology was used the Scientific Method, the study was field, and of descriptive type, through surveys aimed at 18 to 25 year old citizens of the Riobamba urban sector. In addition, interviews were made with characters such as Lenin Garcés, historian riobambeño and Guillermo Montoya, president of the Casa de la Cultura Ecuatoriana Núcleo de Chimborazo.In addition, the results obtained are collated with the theoretical contributions in the development of their discussion. As a conclusion, it is worth noting that since the construction of imaginary in relation to its surroundings has been creating a high level of knowledge and belonging to Riobamba as a Novelty City. It is important to mention them, since the Primera Asamblea Constituyente, Radio El Prado, Bellavista, among others, are elements that represent their identity and recognition.Finally, given the need not having communication products that conceive of Riobamba as a Novelty City, it is suggested to compile information that determines it as such, in order to generate a greater diffusion, awareness and guarantee of its historical relevance in context.